Gaseous fuels production from dried sewage sludge via air gasification. Issue 7 (July 2014) - Werle, Sebastian; Dudziak, Mariusz
Gasification is a perspective alternative method of dried sewage sludge thermal treatment. For the purpose of experimental investigations, a laboratory fixed-bed gasifier installation was designed and built. Two sewage sludge (SS) feedstocks, taken from two typical Polish wastewater treatment systems, were analysed: SS1, from a mechanical-biological wastewater treatment system with anaerobic stabilization (fermentation) and high temperature drying; and (SS2) from a mechanical-biological-chemical wastewater treatment system with fermentation and low temperature drying. The gasification results show that greater oxygen content in sewage sludge has a strong influence on the properties of the produced gas. Increasing the air flow caused a decrease in the heating value of the produced gas. Higher hydrogen content in the sewage sludge (from SS1) affected the produced gas composition, which was characterized by high concentrations of combustible components. In the case of the SS1 gasification, ash, charcoal, and tar were produced as byproducts. In the case of SS2 gasification, only ash and tar were produced. SS1 and solid byproducts from its gasification (ash and charcoal) were characterized by lower toxicity in comparison to SS2. However, in all analysed cases, tar samples were toxic.